Report of seven children with hepatopulmonary syndrome - Erge, Duygu; Selimoğlu, Mukadder Ayşe; Karakurt, Cemşit; Karabiber, Hamza; Elkıran, Özlem; Çatal, Ferat; Koroğlu, Reyhan (Turkish Journal of Gastroenterology, 2014)
Abstract Hepatopulmonary syndrome is an important pulmonary vascular complication of liver disease. Its diagnosis is based on the presence of hypoxaemia and the demonstration of intrapulmonary shunting by contrast-enhanced echocardiography or perfusion lung scanning. Awareness of this condition is critical to improve the outcomes of patients with chronic liver disease and/or portal hypertension because hepatopulmonary syndrome receives additional priority on the waiting list for transplantation. A non-invasive measurement of the blood oxygen saturation with pulse oximetry is recommended as a screening tool for this syndrome. The aim of this report was to present clinical and laboratory findings and follow-up of seven paediatric patients who were diagnosed with HPS at our centre.